Regulation as a constitutional principle of economic behavior: the lack of tuning in the telecommunications sector (Law, State and Telecommunications Review, 2009)
CARVALHO, Carlos Eduardo Vieira de. Regulação de Serviços Públicos na Perspectiva da Constituição Econômica Brasileira. Belo Horizonte: Editora Del Rey, 2007, 172p. (R$34,90)